Microbial metagenomic analysis of paddy field soil of Bario, the Kelabit Highland of Sarawak / Supang Lau Mei Ling - Supang Lau , Mei Ling (2018)

(untitled)
Rice is known as one of the staple foods of the world particularly in Asian countries as the largest producer and consumer. The increasing demand and the declining supply of rice in Malaysia had always been an issue and that can only be solved with the imported rice from neighbouring countries. In Malaysia, one of the popular rice varieties comes from Bario, Sarawak and it is widely known as Bario rice. Bario rice is known as a unique form of delicacy in Malaysia. The farmers have been practicing traditional wet rice cultivation for centuries. This study aims to have an insight of the microbial community profile and the genes that involves in nutrient cycling in the paddy field soils obtained from Bario, Kelabit Highland of Sarawak using next-generation sequencing (NGS) approach. The DNA of the paddy field soils were extracted using Power Soil DNA Isolation Kit (MOBIO Laboratories, Inc) before subjected to NGS. The raw sequences obtained were trimmed and assembled using CLC Genomic Workbench 7.0. Assembled contigs were identified for the presence of prokaryotic components by BLASTN with GenBank 16S microbial database with e-value of < 10-9. The data obtained from BLAST were analysed for taxonomic distribution using Metagenome Analyzer (MEGAN) version 5.2.3. The assembled contigs were annotated using Prokka, a software tool for rapid annotation of prokaryotic genomes. NGS data revealed immense diversity of ecologically important microbes present in the soil sample belongs to bacteria and archaea domains. The phylum Proteobacteria occupied the highest portion (57%) of the bacteria sequences in the F3F (Field 3F) paddy field soil sample followed by Euryarchaeota (12%), Actinobacteria (6%), Acidobacteria (3%), Verrucomicrobia (2%), Firmicutes (2%), Chloroflexi (2%) and Bacteroidetes (1%). Also, the most predominant microbial genera belong to Geobacter (17%), Candidatus methanoregula (7%), Anaeromyxobacter (7%), Methanosaeta (3%), Opitutus (2%), Burkholderia (2%), Syntrophus (2%), Bradyrhizobium (2%) and Pelobacter (2%). There was a total of 413,191 genes annotated from Prokka and the genes such as ntpJ, ctpV, nikR, narT, yydH, rip3, albF, narG, narY, narI, narV, cysO, zitB and zur that involves in the nutrient cycling of the paddy field soil were identified. In conclusion, a total of 26 phylas, 41 microbial classes, 87 microbial orders, 177 microbial familiae and 388 microbial genera were found from this paddy field soil samples. Each of the microbial communities in the soil plays an important role in nutrient cycling.